Սահմանադրականության մակարդակը որպես պետության կայացածության գրավական - Խաչատրյան, Կառլեն (Bulletin of Yerevan University G: Economics, 2017)
The article examines the relationship between the level of constitutionalism and state capacity. Analysing the main approaches to assessing the state's capacity, the system of indexes of capacity was given in a generalized manner. The article also draws parallels between the indexes of capacity and the indexes of assessment of the level of constitutionalism.
Keywords: state, capacity, constitutionalism, constitutional economy, economic policy, state regulation